2021
DOI: 10.1016/j.ajog.2021.04.228
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine disturbs fetal cardiac function during hypoxemia in a chronic sheep model at near term gestation

Abstract: BACKGROUND: Nifedipine is a widely used drug in pregnancies complicated by maternal hypertensive disorders that can be associated with placental insufficiency and fetal hypoxemia. The evidence regarding fetal myocardial responses to nifedipine in hypoxemia is limited. OBJECTIVE: We hypothesized that nifedipine would not impair fetal sheep cardiac function under hypoxemic environment. In particular, we investigated the effects of nifedipine on fetal ventricular functional parameters and cardiac output. STUDY DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In this study, RV-GLS values were shown to be significantly higher throughout pregnancy compared with LV-GLS values. This finding is consistent with the results of other studies comparing LV-GLS and RV-GLS with advancing gestation 34,64,66 and in neonates 67 . Differences in ventricular myocardial architecture can explain the difference in GLS values between the two ventricles 68,69 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, RV-GLS values were shown to be significantly higher throughout pregnancy compared with LV-GLS values. This finding is consistent with the results of other studies comparing LV-GLS and RV-GLS with advancing gestation 34,64,66 and in neonates 67 . Differences in ventricular myocardial architecture can explain the difference in GLS values between the two ventricles 68,69 .…”
Section: Discussionsupporting
confidence: 93%
“…The majority of its output is via the arterial duct and the descending aorta, as the pulmonary resistance is high due to the uninflated fluid-filled lungs limiting pulmonary blood flow 1 . In late gestation, with increased ductal sensitivity to changes in oxygen, saturation increases and this, along with placental maturation and increasing fetal blood pressure, affects the right ventricular afterload 1,63,64 . Changes in preload and afterload of both ventricles will be reflected in increased GLS and GLSR values.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, sheep models used to answer research questions for humans often did not focus on animal survival. Even in studies with a neonatal focus, lambs and/or ewes have often been sacrificed [ 3 , 15 , 16 , 34 ]. As a result, there is little detailed information on how to follow up sheep after a planned CD, which represents a hurdle for obstetric researchers in developing new sheep models while maintaining animal welfare.…”
Section: Discussionmentioning
confidence: 99%
“…As CD is an operation that both the ewe and the lambs can survive, contemporary ethical and animal welfare considerations—such as the 3R principle—demand an appropriate study design that promotes maternal as well as neonatal well-being [ 14 ]. However, information on these topics is scarce, as it is still a common practice to euthanize both ewes and lambs after experiments [ 15 , 16 ]. Existing veterinary publications deal with the technique of performing CD under field conditions [ 17 – 21 ] and focus on emergency CD of ewes under labor due to complications such as failure of the cervix to dilate, fetal-maternal disproportion, or fetal malpresentation [ 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent study [16] in 2021, pointed the detrimental effect of Nifedipine on hypoxic fetus. From a clinical perspective, Nifedipine is a widely used medication in hypertensive patients where restricted fetal growth is not uncommon.…”
Section: Discussionmentioning
confidence: 99%